Association of systemic immune-inflammation index with all-cause and cardio-cerebrovascular mortality in individuals with diabetic kidney disease: evidence from NHANES 1999-2018 - Zhang, Manhuai; Ye, Siyang; Li, Jianbo; Zhang, Meng; Tan, Li; Wang, Yiqin; Xie, Peichen; Peng, Huajing; Li, Suchun; Chen, Sixiu; Wen, Qiong; Chan, Kam Wa; et al. (Frontiers in Endocrinology, 2024)
Background: Emerging evidence suggests a potential role of immune response and inflammation in the pathogenesis of diabetic kidney disease (DKD). The systemic immuneinflammation index (SII) offers a comprehensive measure of inflammation; however, its relationship with the prognosis of DKD patients remains unclear.Methods: Using data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2018, this cross-sectional study involved adults diagnosed with DKD. Cox proportional hazards models were utilized to assess the associations between SII and all-cause or cardio-cerebrovascular disease mortality. Additionally, restricted cubic spline, piecewise linear regression, and subgroup analyses were performed.Results: Over a median follow-up duration of 6.16 years, 1338 all-cause deaths were recorded.After adjusting for covariates, elevated SII levels were significantly associated with increased risks of all-cause and cardio-cerebrovascular disease mortality. Specifically, per one-unit increment in natural log-transformed SII (lnSII), there was a 29% increased risk of all-cause mortality (P < 0.001) and a 23% increased risk of cardio-cerebrovascular disease mortality (P = 0.01) in the fully adjusted model. Similar results were observed when SII was analyzed as a categorical variable (quartiles). Moreover, nonlinear association was identified between SII and all-cause mortality (P < 0.001) through restricted cubic spline analysis, with threshold value of 5.82 for lnSII. The robustness of these findings was confirmed in subgroup analyses. Likewise, the statistically significant correlation between SII levels and cardio-cerebrovascular disease mortality persisted in individuals with DKD.Increased SII levels, whether examined as continuous variables or categorized, demonstrate a significant association with elevated risks of all-cause and cardiocerebrovascular disease mortality among DKD patients. These findings imply that maintaining SII within an optimal range could be crucial in reducing mortality risk.